1985
DOI: 10.1002/ijc.2910350211
|View full text |Cite
|
Sign up to set email alerts
|

Transfection by human oncogenes: Concomitant induction of tumorigenicity and tumor‐associated membrane alterations

Abstract: NIH 3T3 cells were transfected with DNA derived from human bladder carcinoma, colon carcinoma and HL60 promyelocytic leukemia cells. The transfectants were examined for the presence of human oncogenes in relation to tumorigenic potential and composition of surface-located fucosyl glycopeptides by gel filtration, Concanavalin-A-binding and high-performance liquid chromatography. All transfectants, harboring 3 different human cellular ras genes, appeared to be tumorigenic in nude mice and displayed characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…Consequently, their metabolic shift to an increased sialic acid density, at least of some sialoglycoproteins responsible, may bring about the enhanced metastasis, especially invasiveness. This is also consistent with other work demonstrating good correlations between sialic acid contents and invasiveness [4,6,8,9]. We have further found that BL6 cells, a high invasive variant of B16 melanoma cells, have higher levels of sialyltransferase activity than cells of low invasiveness, although in that case sialidase activity was hardly affected (unpublished data).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consequently, their metabolic shift to an increased sialic acid density, at least of some sialoglycoproteins responsible, may bring about the enhanced metastasis, especially invasiveness. This is also consistent with other work demonstrating good correlations between sialic acid contents and invasiveness [4,6,8,9]. We have further found that BL6 cells, a high invasive variant of B16 melanoma cells, have higher levels of sialyltransferase activity than cells of low invasiveness, although in that case sialidase activity was hardly affected (unpublished data).…”
Section: Discussionsupporting
confidence: 93%
“…The changes generally involve glycoproteins expressed on tumor cell surface with increased branching of complex-type N-glycans, increased polylactosaminoglycan chains and increased sialylation [l-5], which are correlated not only with tumorigenicity but also with elevated metastatic potential [6,7]. In particular, the alterations in sialylation have been proposed to be intimately associated with invasiveness and metastatic ability [4,6,8,9]. To elucidate how such aberrant sialylation occurs in cancer cells, we have been studying sialidase and sialyltransferase in rat hepatoma [lo-121 and other tumor models [13].…”
Section: Introductionmentioning
confidence: 99%
“…36 To investigate these survival pathways and their importance in impeding apoptosis, we used the acute pro-myeloid leukaemic cell line, HL60, which has an activating N-Ras mutation. 37,38 Furthermore, HL60 cells, although highly expressing Bcl-2 are unselected for enhanced resistance to cytotoxic drugs. 39 This is relatively uncommon in drug resistance studies which often employ cell lines which have been artificially selected for high levels of resistance to concentrations of drugs which may never be clinically relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Ras-expressing cells develop a constellation of new features. Some of these could be expected to favour autonomous growth, such as the production of tumour growth factors (Ozanne et al, 1982;Anzano et al, 1985;Pragnell et al, 1985;Spandidos, 1985;Marshall et al, 1985) and release from pre-existing control by exogenous trophic stimuli (Kasid et al, 1985;Racker et al, 1985;Zahn & Goldfarb, 1986), whilst some correlate strongly with invasive and metastatic ability, such as increased sialylation of surface glycoproteins (Collard et al, 1985). Ras gene expression, however, is also associated with enhanced cellular capacity to act as a target for NK cytocidal activity (Johnson et al, 1985;Trimble et al, 1986) a feature likely to militate against successful metastasis (Nicolson & Poste, 1983;Hanna & Schneider, 1983).…”
mentioning
confidence: 99%